2024
DOI: 10.1038/s41598-024-55983-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of astrocyte-derived extracellular vesicles over the first month post-stroke in humans

Matthew A. Edwardson,
Masato Mitsuhashi,
Dennis Van Epps

Abstract: We sought to identify alterations in the quantity of plasma brain-derived extracellular vesicles (EV) over the first month post-stroke to shed light on related injury and repair mechanisms. We assessed plasma levels of presumed neuron-derived EVs (NDEs), astrocyte-derived EVs (ADEs), and oligodendrocyte-derived EVs (ODEs) in 58 patients 5, 15, and 30 days post-ischemic stroke and 46 controls matched for cardiovascular risk factors using sandwich immunoassays. Subsets of brain-derived EVs were identified by co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Astrocytes are critical factors in mediating ischemic damage, with many functions regulated by cellular cross talk through EVs. A recent study revealed preferentially increased ADEV levels over the first month (from 5 to 30 days) post-IS in humans, possibly due to their trophic support on ischemia-damaged neurons; still, the cargo of these EVs has not been assessed [ 45 ]. As a highly specific marker of astrocyte activation, the GFAP is considered a promising prognostic biomarker with clinical utility [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes are critical factors in mediating ischemic damage, with many functions regulated by cellular cross talk through EVs. A recent study revealed preferentially increased ADEV levels over the first month (from 5 to 30 days) post-IS in humans, possibly due to their trophic support on ischemia-damaged neurons; still, the cargo of these EVs has not been assessed [ 45 ]. As a highly specific marker of astrocyte activation, the GFAP is considered a promising prognostic biomarker with clinical utility [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons may be that five out of the nine patients receiving thrombolysis had ischemic lesions on CT scans at D1 after stroke onset. Similarly, a recent study assessing ADEV levels in IS patients—but not their cargo—found no significant differences between participants who did or did not receive IV tPA (alteplase) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%